(untitled) (Journal of Information Systems and Technology Management, 2015)
This paper's main contribution is the description of the process and experience in developing Information and Communication Technology strategic planning at a Brazilian public higher education institution. Action research was used as the scientific method and each of its research steps are presented. It also presents the instruments that were built for assessing organizational needs, the institutional diagnosis form, the required adaptations in the SISP ICT strategic planning model, as well as the reflections about the ICT strategic development process for this particular organizational context. The results evidence the feasibility of use and adaptability of the SISP ICT strategic planning model, enabling the effective ICT strategic development in similar contexts.